2021
DOI: 10.1021/acs.inorgchem.1c02001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Precursor Route to Bournonite (CuPbSbS3) Thin Films and Powders

Abstract: Quaternary metal chalcogenides have attracted attention as candidates for absorber materials for inexpensive and sustainable solar energy generation. One of these materials, bournonite (orthorhombic CuPbSbS 3 ), has attracted much interest of late for its properties commensurate with photovoltaic energy conversion. This paper outlines the synthesis of bournonite for the first time by a discrete molecular precursor strategy. The metal dithiocarbamate complexes bis(diethyldithiocarbamato)c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Lewis's research group has extensively explored the versatility of metal xanthates and thiocarbamates for the phase-pure preparation of various exotic multinary metal sulfides. [14][15][16][17] Similarly, Revaprasadu et al have also investigated the suitability of xanthates and thiocarbamates for the preparation of several important nanosized metal sulfides. [18][19][20] However, a thorough literature study has revealed that xanthates have not been explored for the preparation of technologically important Cu 2 GeS 3 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis's research group has extensively explored the versatility of metal xanthates and thiocarbamates for the phase-pure preparation of various exotic multinary metal sulfides. [14][15][16][17] Similarly, Revaprasadu et al have also investigated the suitability of xanthates and thiocarbamates for the preparation of several important nanosized metal sulfides. [18][19][20] However, a thorough literature study has revealed that xanthates have not been explored for the preparation of technologically important Cu 2 GeS 3 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…It is well reported in the literature that the volatile nature and possibility of sublimation at an elevated temperature in some antimony complexes with a sulfur-containing ligand restrict the exact determination of the nature of residue on the basis of weight loss percentage. 42,43 In order to investigate the nature of residue, the complex 1 was furnace heated at a rate of 10 °C min −1 under flowing Ar up to 330 °C. The temperature was maintained for 1 h, after which the heating was stopped and the furnace was cooled to room temperature under flowing Ar.…”
Section: Thermal Studiesmentioning
confidence: 99%
“…In fact, solutions could also be utilized in CVD, such as with aerosol-assisted CVD (AACVD). As an emerging method with a large potential in industrial applications, AACVD has been widely used in the thin-film deposition of traditional functional materials, such as transparent conducting oxides and superhydrophobic materials. , Recently, semiconductor films of perovskites, bournonites, and their derivatives deposited via AACVD have also been investigated as the absorber layer in solar cells. , AACVD combines the benefits of solution- and vapor-based deposition. There are basically two kinds of AACVD setups, including hot-wall and cold-wall reactor (Figure ).…”
Section: Aerosol-assisted Cvd (Aacvd)mentioning
confidence: 99%